Obligations and Responsibilities of Parents of Sexually Disoriented Persons towards Minors as Legal Relations Due to Marriage and Blood Relations - Komalawati, Veronica; Nasution, Fatmi Utarie; Amanda, Marsya Rindu (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
In Indonesian positive law, the obligations and responsibilities of parents towards children are regulated in Article 45 of Law No. 1 of 1974 concerning Marriage and Article 77 paragraph 3 of the Compilation of Islamic Law. The obligations and responsibilities of parents with sexual disorientation towards children tend to be unfulfilled because the sexual disorientation behavior threatens the child's growth and development reasonably. This study aims to know and understand the obligations and responsibilities of parents towards minors in the event of divorce associated with Law No. 35 of 2014 concerning Child Protection based on the Marriage Law and IHL and find and formulate legal consequences for parental obligations and responsibilities if parents experience sexual disorientation based on the Marriage Law and KHI. This research was conducted using normative juridical methods with analytical descriptive research specifications. The author relates the problem comprehensively based on relevant laws and regulations. The data collection technique used is a literature study. The results showed that the obligations and responsibilities of parents in the form of maintaining and educating children are an attachment that will not be broken even though the marriage of both parents ends. Sexual disorientation suffered by parents can threaten the child's growth and development naturally, resulting in legal consequences, namely the revocation of parental power. However, it does not necessarily eliminate all obligations and responsibilities as parents.